Determinants of Exclusive Breastfeeding Practices Among Informal Sector Working Mothers - Lu'lu Nafisah; Yuditha Nindya Kartika Rizqi; Leni Maryati (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Exclusive Breastfeeding (EBF) is essential for optimal infant growth, development, and disease protection.  Despite its well-documented benefits, global EBF rates remain suboptimal, and the rate in Indonesia (52%) remains below the WHO's 2030 target. This study investigates factors affecting EBF among working mothers in the informal sector in Banyumas Regency, Indonesia, a particularly vulnerable group facing challenges like inadequate maternity leave and limited workplace support. A cross-sectional study was conducted with 350 informal sector working mothers. Data on sociodemographic, maternal, work-related, and social factors were collected using a validated and reliable questionnaire and analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) methods.  The results showed that 68.2% of mothers successfully practiced EBF, a slightly higher rate than reported in previous studies. Multivariate analysis revealed that strong family support (AOR=18.098, 95% CI: 7.396 – 44.285, p<0.001), mother's good knowledge, and positive attitudes were powerful enablers of EBF. Conversely, several counter-intuitive associations were found: lower maternal education (AOR=16.008, 95% CI: 3.422 – 74.894, p<0.001), longer work duration (>8 hours/day; AOR=7.434, 95% CI: 3.364 – 16.426, p<0.001), primiparous status (AOR=3.998, 95% CI: 1.830 – 8.734, p=0.001), non-performance of immediate breastfeeding (AOR=8.535, 95% CI: 3.523 – 20.675, p<0.001), and non-consumption of breast milk boosters (AOR=5.229, 95% CI: 1.284 – 21.291, p=0.021) were all independently associated with a higher likelihood of EBF. Maternal age was not found to be a significant determinant. This study revealed highly complex, context-specific determinants of exclusive breastfeeding (EBF) among informal sector working mothers, often diverging from patterns observed in formally employed populations. Key findings underscore the need for tailored, context-sensitive interventions focusing on strengthening informal social support, advocating for adaptive work accommodations, and providing targeted education.